Impact of mRNA-assessed molecular subtype conversion, intact and apoptotic circulating tumor cells on survival of metastatic breast cancer patients: proof of principle - Stefanovic, Stefan; Deutsch, Thomas M.; Wirtz, Ralph; Hartkopf, Andreas; Sinn, Peter; Kohler, Maximilian; Hofmann, Jan; Bankovic, Sanja; Vassilev, Katja; Sütterlin, Marc; Schneeweiss, Andreas; Wallwiener, Markus (Diagnostics, 2020)
Breast cancers (BC) can mutate, allowing metastatic tumors (MT) to sometimes differ to primary tumors (PT) in gene expression. Despite contemporary metastatic breast cancer (MBC) therapy, subtype conversion seems prognostically disadvantageous. We strived to determine the influence of mRNA-assessed intrinsic subtype stability comparing PT and MT biopsies and circulating tumor cell (CTC)-based liquid biopsies on progression free survival (PFS) and overall survival (OS). Additional analyzed prognostic factors were PT subtype, MT subtype and hormone receptor loss. Kaplan-Meier curves and the log rank tests were used to compare PFSs and OSs. The proportions of luminal B and triple negative subtype MTs were increased compared to those observed in PTs. Fifteen patients were found to have tumors that underwent intrinsic subtype conversion and their OS was significantly decreased (p= 0.038). No such difference was observed when it comes to PFS. The majority of these tumors switched to a more aggressive intrinsic subtype. No significant differences in PFSs or OSs were observed between subtype converters with triple negative PTs compared to those with luminal subtype PTs. The same is true of subtype stable patients. Total CTC, iCTC and aCTC counts decreased with therapy, but there were no significant differences between subtype converters and subtype stable patients. Our data confirm a poorer overall survival of the intrinsic subtype converters and emphasize the importance of acquiring biopsies and re-biopsies of all available metastatic lesions alongside with CTC-based liquid biopsies for earlier recognition of patients with poorer prognosis and in need of altered individualized therapy regimens.
Gesehen am 26.10.2020